Efficacy and safety of phacotrabeculectomy versus phacogoniotomy in advanced primary angle-closure glaucoma: study protocol for a multicentre non-inferiority randomised controlled trial (PVP Study) - Xiulan Zhang; Xi Zhang; Yi Zhang; Li Tang; Guangxian Tang; Hengli Zhang; Aiguo Lv; Huiping Yuan; Yunhe Song; Lin Xie; Lan Lu; Kun Hu; et al. (BMJ Open)
Introduction Primary angle-closure glaucoma (PACG) has a high prevalence and blinding rate across Asia. The first-line treatment of PACG is surgery, and phacotrabeculectomy remains the mainstream surgery for advanced PACG. However, it may cause vision-threatening complications with long learning curve. Minimally invasive glaucoma surgery has been gradually used in PACG combined with cataract surgery and achieved efficacy without excessive injury, of which goniotomy is the most commonly performed. Therefore, this study aimed to conduct a multicentre, non-inferiority randomised controlled clinical trial to compare the efficacy and safety of phacotrabeculectomy versus phacogoniotomy in advanced PACG.Methods and analysis This is a non-inferiority multicentre randomised controlled trial and will be conducted at eight ophthalmic departments and institutes in China. 124 patients with advanced PACG will be enrolled and randomised to undergo phacotrabeculectomy or phacogoniotomy. Comprehensive ophthalmic examinations will be performed before and after the surgery. The primary outcome is the change of intraocular pressure at 12 months after surgery compared with the baseline intraocular pressure. An extended follow-up period of 36 months will be required. Cumulative success rate of surgery, intraoperative and postoperative complications, and number of anti-glaucomatous medications will also be compared between the groups as secondary outcomes.Ethics and dissemination Ethical approval has been obtained from the ethical committee of Zhongshan Ophthalmic Center, Sun Yat-sen University, China (ID: 2021KYPJ090) and all subcentres. All the participants will be required to provide written informed consent. The results will be disseminated through scientific meetings and published in peer-reviewed journals.Trial registration number NCT04878458.